Methodology for Group Bonding Nutritional Counseling - Alvarado Molina, Nadia; Ureña Retana, Ivannia; deBeausset Stanton, Indira (Población y Salud en Mesoamérica, 2022)
Introduction: This essay presents the methodology for Group Bonding Nutritional Counseling (GBNC), which has been developed at the School of Nutrition at the University of Costa Rica in recent decades. In relation to GBNC, the objectives are: 1) To present the epistemological foundations; 2) To show the methodology on how to develop the group bonding nutritional counseling; and 3) To describe the desirable soft skills for the facilitator in a group bonding nutritional counseling process. GBNC’s conceptual approach is centered on the patient as a person exercising their autonomy and agency over their life, and how GBNC helps in the resolution of obstacles for better treatment adherence. GBNC´s methodological approach is based on Pichon-Rivière’s operative groups which was adapted for nutritional counseling. Proposition: GBNC goes beyond group interactive nutrition education and includes all the steps to nutritional care, including individual follow ups. GBNC’s methodology has robust theoretical background, as well as adequate settings for its implementation, evaluation, and use. Arguments for discussion: For the past decades, the School of Nutrition at the University of Costa Rica has developed the methodological framework for GBNC: from its theory foundation, useful soft skills for the facilitator to conduct, guide and support groups to focus on the task, and proficiently to handle the vectors of group dynamics. GBNC is useful for people to work on improving their health as it allows them to face daily barriers they encounter. Conclusions: GBNC has great methodological potential for group support in the treatment of adults with chronic diseases; it is inexpensive and improves time management and human resources in nutritional care. In addition, it allows patients to exercise their autonomy, agency, and problem-solving skills in a safe space, within the containment of the group and the nutritionist.